Chimpanzee lip-smacking facilitates cooperative behaviour - Fedurek, Pawel; Slocombe, Katie E.; Hartel, Jessica A.; Zuberbühler, Klaus (My University, 2015)
Signalling plays an important role in facilitating and maintaining affiliative or cooperative interactions in social animals. Social grooming in primates is an example of an interaction that requires coordination between partners but little is known about communicative behaviours facilitating this activity. In this study, we analysed the communication of wild chimpanzees of Budongo Forest, Uganda, as they entered and maintained a naturally occurring cooperative interaction: social grooming. We found that lip-smacking, a distinct multimodal oral gesture produced during grooming, coordinated this activity. Lip-smacking at the beginning of grooming bouts was significantly more often followed by longer and reciprocated bouts than silent grooming initiations. Lip-smacks were more likely to be produced when the risk of termination of the interaction by the recipient was high, for instance when grooming vulnerable body parts. Groomers were also more likely to produce lip-smacks during face-to-face grooming where the visual aspect of the signal could be perceived. Data are consistent with the hypothesis that chimpanzee lip-smacks function to coordinate and prolong social grooming, suggesting that this oral signal is an example of a communicative behaviour facilitating cooperative behaviour in chimpanzees.